Classification of Terms Related to Uzbek Theater - Kozimova Zumriniso Ismailovna (Zien Journals, 2024)
In the classification of terms related to each field, they are divided into certain thematic groups. It can be seen that there are a number of thematic groups in the classification of Uzbek theater terms. This article analyzes the Uzbek language terms by dividing them into thematic and lexicalsemantic groups.
Keywords: theater; term; subject; group